Michelangelo - Cook, Diane; Michelangelo Buonarroti, 1475-1564.; Ghiuselev, Iassen (Broomall, Pa. : Mason Crest, 2003)
A biography of the late-fifteenth to mid-sixteenth-century Italian artist Michelangelo Buonarroti, whose first famous work, the Vatican Pieta, was displayed in St. Peter's Basilica when he was only twenty-five years old.
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography -- Juvenile literature; Artists